Deprivasi Relatif dan Prasangka Antar Kelompok - Santhoso, Fauzan Heru; Hakim, Moh Abdul (Faculty of Psychology, Universitas Gadjah Mada, 2012)
The study aimed to measure the influence of relative deprivation toward intergroup prejudice within undergraduate students in the Faculty â€œXâ€ at Universitas Gadjah Mada. The relative deprivation theory predicted that when a person or a group is believed to be having limitation/weakness in comparison to the other people/groups, psychological problems and negative behaviors will be likely to occur. Pettigrew (2008) stated that the relative deprivation experienced by a group is strongly related to the occurrence of intergroup prejudice. This study was conducted by using a quasi-experimental method with pre test â€“ post test control group design. A total of 20 undergraduate students participated in this study, which were grouped into two experimental groups (one group with narrative intervention and one group with narrative and provocation intervention) and one control group, after being selected through a proportional random sampling. Data were collected by using two scales, i.e. relative deprivation scale and intergroup prejudice scale. A one-way ANOVA analysis was used to see the difference between pre- and post-test scores across the three groups. Result of the study showed that relative deprivation did not influence the occurrence of intergroup prejudice. Keywords: relative deprivation, prejudice, intergroup